1981
DOI: 10.1111/j.1439-0485.1981.tb00271.x
|View full text |Cite
|
Sign up to set email alerts
|

Partial Carbon and Energy Budgets of the Bacteriosponge Verohgia fistularis (Porifera: Demospongiae) in Barbados

Abstract: Abstract. The major in situ physiological activities of the common, tropical, West Atlantic demosponge Verongia (=Aplysina) fistularis were determined in order to relate the carbon and energy budgets of this species to the two contrasting patterns documented for bacteriosponges (sponges harbouring large symbiotic bacterial populations) and non‐bacteriosponges (sponges lacking such large bacterial populations and considered “normal” sponges). Measurements of specimen dimensions and exhalant water velocity, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
200
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(216 citation statements)
references
References 30 publications
(8 reference statements)
13
200
3
Order By: Relevance
“…Al− though typical sponges feed primarily on bacterial−sized parti− cles through the microvilli of their choanocytes (e.g., Reiswig 1971;Riisgård and Larsen 2000), in some cases (Leys and Eerkes−Medrano 2006) particle capture is through pseudo− podial extensions of these cells; larger particles (5-50 μm) are often captured by amoebocytes lining the incurrent canal walls (Reiswig 1971). There has also been an increasing apprecia− tion of the role of direct uptake of dissolved organic carbon (e.g., Reiswig 1981;Yahel et al 2003), but it is not yet clear to what extent symbiotic organisms are responsible for the up− take, and if the sponge itself is responsible, what is the mecha− nism of uptake. Other studies have also shown that sponge growth rate is independent of the supply of Dissolved Organic Carbon, suggesting a greater dependence on solid particle consumption (Koopmans and Wijffels 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Al− though typical sponges feed primarily on bacterial−sized parti− cles through the microvilli of their choanocytes (e.g., Reiswig 1971;Riisgård and Larsen 2000), in some cases (Leys and Eerkes−Medrano 2006) particle capture is through pseudo− podial extensions of these cells; larger particles (5-50 μm) are often captured by amoebocytes lining the incurrent canal walls (Reiswig 1971). There has also been an increasing apprecia− tion of the role of direct uptake of dissolved organic carbon (e.g., Reiswig 1981;Yahel et al 2003), but it is not yet clear to what extent symbiotic organisms are responsible for the up− take, and if the sponge itself is responsible, what is the mecha− nism of uptake. Other studies have also shown that sponge growth rate is independent of the supply of Dissolved Organic Carbon, suggesting a greater dependence on solid particle consumption (Koopmans and Wijffels 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The concept of a sponge being largely composed of bacteria has led to the occasionally−used term "bacterio− sponge" to refer to the compound organism (e.g., Reiswig 1981). Individual sponge species have a highly specific com− plement of bacterial taxa within their tissues, which are passed on through reproduction and are sufficiently constrained to al− low phylogenetic reconstructions based on the associated bac− teria (Erpenbeck et al 2002;Steger et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…(Demospongiae: Hadromerida: Polymastiidae). The existence of both high-and low-microbial-abundance sponges is well documented (Vacelet and Donadey, 1977;Reiswig, 1981;Hentschel et al, 2006;Weisz et al, 2008), although the exact reasons for these differences in microbial loads are uncertain. In addition to the well-characterized taxa, such as the Alpha-and Gammaproteobacteria, activity was inferred for uncultivated, sponge-specific lineages within phyla, including the Gemmatimonadetes, Chloroflexi and a taxon of uncertain affiliation related to the sponge-specific 'Poribacteria' (Fieseler et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…As filter feeders, sponges process large quantities of seawater removing significant amounts of suspended particles and mircoorganisms (Duckworth et al, 2006). Overall, microorganisms may constitute up to 60% of the tissue biomass in sponges ('bacteriosponges') (Reiswig, 1981). Sponges and their microbiota have been intensively studied for their biochemical profiles and it has been shown that species-specific microbial communities differ from those in ambient seawater with certain sponges hosting a uniform microbial population in different oceans (Vacelet and Donadey, 1977;Wilkinson, 1978;Schmidt et al, 2000;Webster and Hill, 2001;Hentschel et al, 2002).…”
Section: Introductionmentioning
confidence: 99%